Ultrasound-dependent cytoplasmic internalization of a peptide-sonosensitizer conjugate. Issue 15 (1st August 2017) - Inaba, Yuki; Watanabe, Kazunori; Kitamatsu, Mizuki; Nakata, Eiji; Harada, Atsushi; Ohtsuki, Takashi
Graphical abstract: Abstract: A method to induce cytoplasmic peptide delivery, using ultrasound, was demonstrated using a molecular conjugate of a cell-penetrating peptide (CPP), a functional peptide, and a sonosensitizer. As a model of such molecular conjugates, TatBim-RB, consisting of the Tat CPP, the Bim apoptosis inducing peptide, and the sonosensitizer rose bengal was synthesized. CPPs have been widely used for intracellular delivery of various cargos; however, CPP-fused molecules tend to become entrapped in endosomes, as was observed for TatBim-RB molecules applied to cells. To promote escape of the entrapped TatBim-RB molecules, cells were irradiated with ultrasound, which successfully induced endosomal escape and cytoplasmic dispersion of TatBim-RB, and subsequently apoptosis. Our results suggest that this peptide-sonosensitizer conjugate strategy may facilitate numerous kinds of medicinal chemistry studies, and furthermore, this specific conjugate may exhibit potential as a novel therapeutic agent for the promotion of apoptosis.